Reduksi Noise Salt And Pepper Pada Citra Digital Menggunakan Metode Contraharmonic Mean Filter - Simangunsong, Pandi Barita Nauli (MEANS (Media Informasi Analisa dan Sistem), 2017)
Image is an object that is most often used for personal or public purposes, but the image is very susceptible to interference such as noise or noise where the image is exposed to noise or noise will experience black spots attached to the image. The existence of noise attached to the image needs to be reduced so that the image looks clearer using the contraharmonic mean filter method that can reduce noise in digital images. The image affected by noise after being reduced using the contraharmonic mean filter method, the image is much clearer after being reduced.